USE OF HIGHLIGHTING STRATEGIES IN READING COMPREHENSION AND EFFECTS ON ATTAINMENT IN SELECTED READING SKILLS - Tante, Achu Charles; Sass, Enanga Marie (Innovare Journal of Education, 2023)
This study had two specific research objectives, two research questions and four specific research hypotheses. The study used quasi-experimental research designs. Data were collected using a standardized test. The study had a population of English Language students from secondary schools. The purposive sampling technique was used. The sample consisted of 40 students. The reliability of the instruments was established using Cronbach Alpha, which yielded a reliability coefficient of .70. Data collected were analyzed using the Statistical Package for Social Sciences (SPSS version 24.00). Findings revealed that reading comprehension performances of students taught skimming and scanning in the highlighting strategies were significantly higher than those who were not taught using the highlighting strategies.